Legumes And Oilseed Consumption Frequency - Arusoglu, Gülcan; Ozturk, Ahmet; Firat, Selma; Seyfeli, Yasemin (Progress in Nutrition, 2021)
Introduction: Nuts, seeds and legumes are all nutrient-dense foods. Preclinical and clinical studies show that legumes are functional foods that modulate biological processes that facilitate obesity, including thermogenesis, visceral fat accumulation, and satiety.Purpose: The aim of this study is to determine the consumption of legumes and oilseeds consumed locally in children living in the Kırklareli (Thrace) region and to evaluate their relationship with anthropometric measurements. Methods:. A total of 1075 volunteer students and their families, 513 (47.7%) girls and 569 (52.3%) boys, between the ages of 3-9, studying in pre-school and primary schools, participated in the study. The students’ anthropometric data (body weight, height, waist circumference, neck and wrist circumference) were taken. Results: In this study conducted with 1075 children, 47.7% (513 people) of the participants were girls and 52.3% were boys (562 people). When their legume consumption was examined, it was found that 2.5% every day, 29.3% between 3-5 days a week, 45.3% once a week, 7.2% every 15 days, rarely 7.5% and 8.2% of the participants who stated that they did not consume it. The most common legumes consumed by the participants were dried beans, lentils and chickpeas. The most common oilseeds consumed “3-5 days a week” were determined as walnuts, roasted hazelnuts and almonds. There was no statistically significant effect of legumes and oilseed consumption on anthropometric values. Conclusion: Legumes and oilseed consumption habits did not have a significant effect on growth and development. However, weakness, stunting and obesity continue to be important problems as indicators of insufficient and unbalanced food consumption.